ISLAMIC LEARNING IN NUPELAND (1750-1982) (1983)
Islamic learning in Nupe land started almost concurrently with the inception of Islam into the Nupe country, about the middle of the 18th Century. This followed the practice of Islam which made literacy and acquisition of knowledge incumbent on every muslim. This study has been undertaken primarily to examine the rate at which the traditional Islamic learning has developed in the area and, at the same time, to assess the impact of this traditional system of education upon the Nupe people and their culture. The work is divided into six chapters. The first chapter discusses the Nupe traditional religious practices prior to Islam in order to provide a basis for comparison with Islamic religious practices. Chapter two discusses the establishment of Arabic Schools and the emergence of first Arabic writings Chapter three examines Islamic education generally and assesses its impact upon the Nupe people. The role of the teacher in the traditional system of Islamic education is examined in chapter four, while chapter five discusses some of the characteristics of the traditional Islamic Schools versus those of some Western oriented Schools, which also give Islamic education. The concluding chapter examines the sources of revenue for the two categories of educational institutions and discovers that the Western oriented schools are solely sponsored by the government of the area while the private Arabic Schools are left mainly in the hands of proprietors and private organisations. This implies that Western oriented schools have stronger sources of funds and are, generally, more equipped and more organised than the private Arabic Schools. The chapter closes with some suggestions for, the improvement of the quality of Islamic education generally throughout the Nupe country.